The Commodification of Puri Gede Kaba-Kaba as a Tourism Attraction (International Journal of Interreligious and Intercultural Studies, 2024)
This study was conducted with three main problems, namely (1) Factors causing the commodification of Puri Gede Kaba-Kaba as a tourist attraction in Tabanan Regency; (2) The process of occurrence; and (3) The implications for the economic, religious, and socio-cultural aspects for the people of Kaba-Kaba Village. These three problems were analyzed using phenomenological, commodification, and reception theories. This research uses qualitative analysis techniques with a critical paradigm. The result is that several factors cause the commodification of Puri Gede Kaba-Kaba as a tourist attraction, namely external factors, which consist of external puri and external Kaba-Kaba village. External factors of the puri, namely in the form of support from the village government and the entire Kaba-Kaba village community. External factors outside Kaba-Kaba village, in the form of provincial and state government policies related to tourism development. Then the internal factors of the puri, in the form of strong encouragement from the relatives of the puri commodifies the puri to get additional income to maintain the existence of the puri. Furthermore, the commodification process follows management principles, namely planning, organization, coordination, and control. The commodification of Puri Gede Kaba-Kaba as a tourist attraction has implications for various dimensions of life, such as social, cultural, economic, and religious life.